INVESTIGATION OF THE HUNTINGTIN-HAP40 INTERACTION IN HUNTINGTON’S DISEASE - Williamson, Jennifer (My University, 2013)
Huntington’s disease (HD) is a neurodegenerative disorder caused by the expansion of a polyglutamine tract in the huntingtin protein. The huntingtin protein has many roles in vesicular and endocytic trafficking, which can be modified in HD cells. When mutant huntingtin is expressed in HD, protein levels of the huntingtin interacting protein, Huntingtin-associated protein of 40kDa (HAP40) are increased. This increase in HAP40 protein levels causes the formation of a complex between carboxyl terminal huntingtin, HAP40 and active Rab5 on the early endosome. This complex induces a switch from early endosomal movements on microtubules to movements on actin filaments, greatly reducing both the speed and distance of movement. The main objective of this research is to determine where the interaction occurs between huntingtin and HAP40 on the huntingtin protein. Here we show that HAP40 interacts with the amino terminus of huntingtin, specifically the first 17 amino acids (N17). In co-localization studies, we found that HAP40 co-localizes with the carboxyl terminal fragment of huntingtin corresponding to amino acids 2570-2634; however, GFP trap immunoprecipitation analysis revealed no interaction between the carboxyl terminal fragments of huntingtin and HAP40. An interaction was discovered between HAP40 and N17, which was then confirmed by far western blot. These results demonstrate that HAP40 interacts with N17. By identifying the interaction site between HAP40 and huntingtin, modifications can be explored to prevent the interaction of HAP40 with huntingtin. This would restore motility on microtubules reinstating fast, long-range movements of early endosomes.
Keywords: HAP40; Huntingtin; Huntington's disease; Nervous System Diseases; Nervous System Diseases